Oral administration of the probiotic Lactobacillus fermentum VRI-003 and mucosal immunity in endurance athletes. Issue 4 (13th February 2008) - Cox, A J; Pyne, D B; Saunders, P U; Fricker, P A
Abstract : Objective: To evaluate the ability of a probiotic Lactobacillus fermentum VRI-003 (PCC) to enhance the mucosal immune system of elite athletes. Design and setting: A double-blind, placebo-controlled, crossover trial was conducted over a 4-month period of winter training. Participants: 20 healthy elite male distance runners. Interventions: PCC was given at a daily dose of 1.26×10 10 as a freeze-dried powder in gelatin capsules. Placebo capsules contained an inert excipient. Main outcome measures: Treadmill performance (monthly), mucosal and systemic immunity (monthly), training (daily) and illness (daily) were assessed. Serum cytokine levels, salivary IgA levels and incidence, duration and severity of respiratory tract infections were measured. Results: Subjects reported less than half the number of days of respiratory symptoms during PCC treatment (30 days) compared with placebo (72 days, p<0.001). Illness severity was also lower for episodes occurring during the PCC treatment (p = 0.06). There were no significant differences in the mean change in salivary IgA and IgA1 levels, or in interleukin (IL)4 and IL12 levels, between treatments. However, PCC treatment elicited a twofold (p = 0.07) greater change in whole-blood culture interferon gamma (IFNγ) compared with placebo. No substantial changes in running performance measures were seen over the study period. Conclusions: Prophylactic administration of PCC was associated with a substantial reduction in the number of days and severity of respiratory illness in a cohort of highly trained distance runners. Maintenance of IFNγ levels may be one mechanism underpinning the positive clinical outcomes.